Enhancing the carbon sequestration of high-elevation Eucalyptus plantations in Sri Lanka for future carbon market activities. Issue 5 (3rd September 2021) - Amarasinghe, W.V. Tharindu Dilan; Terada, Toru; Yamamoto, Hirokazu
ABSTRACT: Eucalyptus plantations at higher elevations in Sri Lanka are being confronted by a conflict between their industrial need maintenance and ecological need conservation. Increasing carbon sequestration can offer income through carbon markets to minimize profit reductions. Changing the main species and extending the rotation length (ERL) can increase carbon sequestration; thus, this study aimed to compare the carbon sequestration of Eucalyptus grandis (EG) and Eucalyptus microcorys (EM) and their economic benefits. As a chronosequence approach, EG and EM monocultures were selected for data collection and the above-ground carbon (AGC) was calculated. The AGC of EG at 25 years of age was considered as the baseline (BL) and a linear model with log-transformed explanation variable was used to predict AGC growth with ERL. The economic viability of increased AGC was determined based on the net present value (NPV) and compared with the replanting cost. The BL stock was 175.91 t ha −1, while there is no significant effect of changing the main species to increase carbon sequestration. ERL by 20%, 40% and 60% can increase carbon sequestration by 13.7%, 25.2% and 35.2%, respectively. The NPVs of carbon offsets of ERL indicate that all studied ERLs are profitable; however, NPV is decreasing with the ERL, ERL by 20% recorded the highest NPV.